2022
DOI: 10.1037/dev0001281
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spatial training on mathematics performance: A meta-analysis.

Abstract: Prior research has revealed robust and consistent relations between spatial and mathematical skills. Yet, establishing a causal relation has been met with mixed effects. To better understand whether, to what extent, and under what conditions mathematics performance can be improved through spatial training, we conducted a systematic meta-analysis of the extant literature. Our analysis included 29 studies that used controlled pre-post study designs to test the effects of spatial training on mathematics (N = 3,76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(141 citation statements)
references
References 93 publications
(190 reference statements)
4
135
0
2
Order By: Relevance
“…Importantly, the training of spatial skills can lead to corresponding improvements in mathematics achievement (e.g. Lowrie et al, 2017 , 2018a ; Sorby et al, 2013 ; Sorby & Veurink, 2019 ); however the extent to which this occurs varies according to the age of participants, the design of the intervention program, and the extent to which the mathematical measures are aligned to the skills trained (Hawes et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Importantly, the training of spatial skills can lead to corresponding improvements in mathematics achievement (e.g. Lowrie et al, 2017 , 2018a ; Sorby et al, 2013 ; Sorby & Veurink, 2019 ); however the extent to which this occurs varies according to the age of participants, the design of the intervention program, and the extent to which the mathematical measures are aligned to the skills trained (Hawes et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conversely, the spatial reasoning literature has primarily focused on intrinsic skills. This has demonstrated that the development of intrinsic skills from at least age 3 is particularly important for later spatial reasoning ability and mathematics (Atit et al, 2021;Hawes, Gilligan-Lee & Mix, 2022;Schmitt et al, 2018), yet there is very little knowledge of the relationship between extrinsic spatial skills and mathematics in young children. This Paz, Leseman & Volman, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, skills such as mental rotation and block construction performance have been shown to be associated with later mathematics competence (e.g., Gilligan, Flouri & Farran, 2017;Gunderson et al, 2012;Verdine et al, 2017). Additionally, there is evidence that spatial ability is SPATIAL REASONING IN PRACTICE 6 particularly malleable in childhood (Uttal et al, 2013;Hawes, Gilligan-Lee & Mix, 2022) and that the association between spatial skill and mathematics is causal, with numerous studies finding that spatial ability training also leads to improvements in mathematics performance (Hawes, Gilligan-Lee & Mix, 2022). This evidence demonstrates not only that spatial reasoning is associated with mathematics, but also suggests that it is an important foundation for the development of number and mathematics skills.…”
Section: Associations Between Spatial Reasoning and Mathematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some research conducted in the last decade has found that practicing the completion of spatial tasks results in improvement in students’ STEM outcomes (Cheng & Mix, 2014 ; Hawes et al, 2022 ; Miller & Halpern, 2013 ). Cheng and Mix ( 2014 ) found that practice in solving mental rotation problems leads to better addition and subtraction problem solving skills in primary students.…”
Section: Why Is K-12 Spatial Learning Important?mentioning
confidence: 99%